INTERACTIVE MEDIA DEVELOPMENT WITH ARTICULATE STORYLINE 3 FOR 5TH GRADE MATHEMATICS: VOLUME OF 3D SHAPES - Lail, Khofifatul; Fiantika, Feny Rita; Rusminati, Susi Hermin (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2024)
This research explores the creation of interactive learning materials based on Android for the Mathematics subject, specifically the topic of Volume of 3D Shapes (Cuboids and Cubes) for 5th-grade elementary students. The aim is to provide practical guidance on using Articulate Storyline 3 to create accessible interactive learning materials through Android devices. The research employed a sequential exploratory mixed-methods approach and the ADDIE model in the development process. Validation by subject and media experts obtained scores of 90% (Very Satisfied) and 87% (Very Satisfied). The developed application, “Volume of 3D Shapes,” enables direct interaction with the material, enhancing student engagement and comprehension. This research demonstrates the effectiveness of Articulate Storyline 3 in creating innovative interactive learning media.